PENGARUH KEPUASAN KERJA MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINRJA TENAGA SALES PROMOTION PT. LENOVO INDONESIA DIVISI MOBILE BUSSINES GROUP - Sigit Dani Nugroho; Wahyudin Lukmana Yusup (LPPM Universitas Asa Indonesia, 2018)
Purpose- The purpose of this research is to indentify the influence of job satisfaction, work motivation and work discipline toward the performance of the employees Sales Promotion PT. Lenovo's Indonesia Division of Mobile Business Group. Design/methology/approach- The Survey was conducted to 100 respondents, namely the employees Sales Promotion of PT. Lenovo's Indonesia Division of Mobile Business Group. The method used is descriptive analysis. Findings- The result shows that partially, the independent variables (job satisfaction, work motivation and work discipline) has influence toward the dependent variable (performance employees) reaches significance border of 0,05. So that it can concluded that job satisfaction, work motivation and discipline work gives significant influence to the performance of the employees. And simultaneously, the influence of job satisfaction, work motivation and discipline work toward the performance of the employees reaches 55,35%.